2000
DOI: 10.1038/35050091
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric leaves1 mediates leaf patterning and stem cell function in Arabidopsis

Abstract: Meristem function in plants requires both the maintenance of stem cells and the specification of founder cells from which lateral organs arise. Lateral organs are patterned along proximodistal, dorsoventral and mediolateral axes. Here we show that the Arabidopsis mutant asymmetric leaves1 (as1) disrupts this process. AS1 encodes a myb domain protein, closely related to PHANTASTICA in Antirrhinum and ROUGH SHEATH2 in maize, both of which negatively regulate knotted-class homeobox genes. AS1 negatively regulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
818
3
10

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 708 publications
(863 citation statements)
references
References 28 publications
25
818
3
10
Order By: Relevance
“…Moreover, the cotyledons of 35S::CUC1/as1 stm-1 seedlings bear small epidermal cells and adventitious SAMs. These results are consistent with the previous ®nding that loss of AS1 activity completely suppresses the embryonic and vegetative defects of the stm strong allele (Byrne et al, 2000). It is possible that the adventitious SAM formation in 35S::CUC1/ as1 stm-1 cotyledons utilizes the same mechanism that is used for authentic SAM formation that does not involve STM activity.…”
Section: Cuc1 Induces Adventitious Sams On Cotyledons Through Stm Expsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, the cotyledons of 35S::CUC1/as1 stm-1 seedlings bear small epidermal cells and adventitious SAMs. These results are consistent with the previous ®nding that loss of AS1 activity completely suppresses the embryonic and vegetative defects of the stm strong allele (Byrne et al, 2000). It is possible that the adventitious SAM formation in 35S::CUC1/ as1 stm-1 cotyledons utilizes the same mechanism that is used for authentic SAM formation that does not involve STM activity.…”
Section: Cuc1 Induces Adventitious Sams On Cotyledons Through Stm Expsupporting
confidence: 92%
“…As as1 or as2 could suppress stm-1 phenotypes (Byrne et al, 2000(Byrne et al, , 2002, it was suggested that an unknown pathway, except for activation of STM, can induce embryonic SAM, which is suppressed by AS1 or AS2. Consequently, we can expect that as1 or as2 may also suppress the cuc1 cuc2 phenotype.…”
Section: Cuc1 Induces Adventitious Sams On Cotyledons Through Stm Expmentioning
confidence: 99%
See 3 more Smart Citations